Flexor hallucis longus transfer and composite anterolateral thigh fascio-cutaneous flap for reconstruction of massive chronic and infected Achilles tendon lesion. A case report and review of the literature. - Di Lenarda, Luca; Ramella, Vittorio; Ratti, Chiara; Grezar, Laura; Canton, Gianluca; Papa, Giovanni; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2022)
Achilles tendon reconstruction with substance loss and infection in the overlying soft tissues is a challenge. There is no standardized treatment in literature for these cases. We describe a one-stage tendon reconstruction, using flexor hallucis longus (FHL) tendon transfer and an anterolateral thigh flap with vascularized fascia lata in a patient with re-rupture of the Achilles tendon, soft tissue infection and a tendon defect of 10 cm in length. The surgical procedure has had a successful outcome; patient has recovered normal gait, has recovered complete ankle range of motion with only a partial loss in plantar flexion of the big toe, without any loss in strength. No complications have emerged at follow-up. This technique is promising in treating large Achilles tendon defects with overlying soft tissue infection in a one-stage procedure.